2013
DOI: 10.1681/asn.2012080772
|View full text |Cite
|
Sign up to set email alerts
|

Renal CD133+/CD73+ Progenitors Produce Erythropoietin under Hypoxia and Prolyl Hydroxylase Inhibition

Abstract: The identity of the peritubular population of cells with mesenchymal phenotype thought responsible for producing erythropoietin in humans remains unclear. Here, renal CD133 + /CD73 + progenitor cells, isolated from the human renal inner medulla and described as a population of mesenchymal progenitors, released erythropoietin under hypoxic conditions. CD133 2 cells did not synthesize erythropoietin, and CD133 + progenitor cells stopped producing erythropoietin when they differentiated and acquired an epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…CD133 + cells were previously shown to release EPO under hypoxia12, and we have also here confirmed their capacity with respect to human fibroblasts, that were used as controls in our study. The role of CD133 + cells in physiological EPO synthesis within the nephron is unclear, as EPO production has been reported to occur in the peritubular interstitial fibroblasts464748.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…CD133 + cells were previously shown to release EPO under hypoxia12, and we have also here confirmed their capacity with respect to human fibroblasts, that were used as controls in our study. The role of CD133 + cells in physiological EPO synthesis within the nephron is unclear, as EPO production has been reported to occur in the peritubular interstitial fibroblasts464748.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously reported EPO production by CD133 + cells from the medulla under hypoxia in a HIF-2 dependent manner12. In culture, CD133 + cells but not fibroblasts secreted EPO (Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…REPCs, which have long projections between tubules and blood vessels, are detected in the interstitium (8)(9)(10)(11)(12)(13). Lineage-tracing studies have revealed that the majority of REPCs in the healthy kidney are derived from myelin protein 0-expressing (P0-expressing) cells, which are positive for CD73 (also known as ecto-5â€Č-nucleotidase), PDGFRÎČ, and p75 nerve growth factor receptor and negative for PECAM-1 (also known as CD31) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the administration of CD133 + cells in murine models of glycerol‐induced acute kidney injury and of adriamycin‐induced glomerular damage showed improvement of the renal function, suggesting the feasibility of cell therapy with human isolated CD133 + renal progenitors [56, 57, 61, 62]. However, at present, the possible application of these cells cannot be envisaged, for several reasons such as the scarce availability of the cells, the need for compatibility among patients, and the availability of other sources of effective cells as MSCs.…”
Section: Modulation Of Resident Progenitor Cellsmentioning
confidence: 99%